Effectiveness of Cooperative Integrated Reading and Composition (CIRC) Model Assisted by Media Puzzle on Nonfiction Writing Skills Class IV SDN Tajungsari 02 Pati - Yuliatin, Diah; Suyitno, Suyitno; Wijayanti, Arfilia (Universitas Nusantara PGRI Kediri, 2019)
Based on school observations the teacher still uses the lecture method and does not use learning and learning media still centered on the teacher. So that the writing skills of fourth-grade students of SD Negeri Tajungsari 02 Pati showed that 40% of students already had good writing skills, while 60% of students still had low writing skills. From these problems, the purpose of this study was to describe the effectiveness of the Cooperative Integrated Reading And Composition model assisted by media puzzles for the fourth-grade nonfiction writing skills of SDN Tajungsari 02 Pati. This research is a quantitative study using a pre-experimental design with the type One-Grup Pretest-Posttest. The data analysis technique used the t-test on the pretest and posttest values, the results of the study were calculated by the statistical formula, after being treated using Media CIRC model Puzzle there was an increase in nonfiction writing skills, it was seen that the final results of writing skills student nonfiction have increased. It was proven by t-test obtained pretest > posttest that is 24.5695> 2.021 then Ho was rejected and Ha was accepted meaning Cooperative Integrated Reading And Composition model was assisted by media puzzle effective on nonfiction writing skills of IVSD class of Tajungsari 02 Pati.